Efectos de tratamientos de plasma frío en la preservación de la calidad de manzanas mínimamente procesadas - Denoya, Gabriela Inés (2022)
Strategies to preserve minimally processed fruits pose a challenge technological, since they must maintain the freshness of whole fruits when deterioration is accelerated by processing. Therefore, cold plasma technology is proposed as an alternative. By applying electrical energy to a gas, active compounds (radicals, UV photons and charged particles) are produced that can contribute to the preservation of these products. The evaluated treatments proved to be adequate to preserve the quality of the apple slices. However, the treatments failed to totally inactivate polyphenol oxidase and, therefore, neither stabilize the antioxidant content of the samples during storage, so it must be evaluate the combination with other preservation strategies in future studies.